Study on support time of tunnel lining based on non-equilibrium evolution. Issue 5 (October 2021) - Deng, J.Q.; Cui, W.; Zhu, Y.B.; Liu, Y.; Du, S.L.
Abstract: According to non-equilibrium evolution stability and control theory, over force is the internal effective driving force of unrecoverable time-dependent deformation. The distribution of over force reflects the failure position and mode of tunnel. The opposite force of over force is the optimal reinforcement force to prevent unrecoverable time-dependent deformation and provides a quantitative and accurate reinforcement design method for tunnel. The plastic complementary energy (PCE) is the norm of over force. The curve of PCE versus time provides a unified quantitative criterion of real time dynamic stability evaluation of tunnel in time-dependent deformation process under various external disturbing factors. Based on the curve of PCE versus time, the stresses of lining structure in different supporting time after excavation are studied comparatively. The results show that the stress of lining structure will be very high if supporting time is too early. The surrounding rock of tunnel will be unstable due to damage evolution if supporting time is too late. There is an optimal supporting time when the stress of lining structure will not be too high and the surrounding rock will not lose stability. The curve of PCE versus time can be used to guide reinforcement design and evaluate reinforcement effect.